2016
DOI: 10.1097/spc.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early palliative care on the quality of care during the last days of life: what does the evidence say?

Abstract: The evidence from randomized controlled trials supports the integration of palliative care early in the disease trajectory. However, in terms of outcomes and quality indicators for care in the last days of life, evidence is still lacking. Predominantly, when it comes to the outcomes which may be more difficult to assess, such as spiritual aspects, or the social network, for which more comprehensive information is needed. These outcomes should not be neglected in palliative care studies, particularly when they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(33 reference statements)
0
9
0
2
Order By: Relevance
“…In our study, we found that patients who received palliative care and their FCs have more needs than those who did not receive palliative care. Although, it can be expected that those who received palliative care are more ill (tended to be inpatients and lower KPS) and therefore have more needs, as early palliative care has been proven to improve the QOL of the patients with advanced cancer [ 52 56 ], we postulate that this may also imply that patients with advanced cancer were referred by their oncologists to palliative care physicians late in their cancer trajectory. This late referral may have resulted in patients who are more ill and therefore, have more needs and require more care.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that patients who received palliative care and their FCs have more needs than those who did not receive palliative care. Although, it can be expected that those who received palliative care are more ill (tended to be inpatients and lower KPS) and therefore have more needs, as early palliative care has been proven to improve the QOL of the patients with advanced cancer [ 52 56 ], we postulate that this may also imply that patients with advanced cancer were referred by their oncologists to palliative care physicians late in their cancer trajectory. This late referral may have resulted in patients who are more ill and therefore, have more needs and require more care.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple organizations 14 emphasize that palliative care interventions should be initiated early in the disease trajectory and support advance care planning (ACP) 5 for patients with serious, life-limiting illnesses alongside disease modifying treatment. 3,6 Early palliative care, including ACP, involves complex interventions 7 in which professionals discuss symptom management, support end-of-life decision-making and coordinate care.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple organizations [1][2][3][4] emphasize that palliative care interventions should be initiated early in the disease trajectory and support advance care planning (ACP) 5 for patients with serious, life-limiting illnesses alongside disease modifying treatment. 3,6 Early palliative care, including ACP, involves complex interventions 7 in which professionals discuss symptom management, support end-of-life decision-making and coordinate care. Intervention trials 6,[8][9][10][11][12][13][14][15][16][17][18][19] confirm that patients with advanced cancer who receive early palliative care experience improved quality of life, 6,[19][20][21] symptoms, 6,19 and mood, 6 are more likely to document end-of-life care decisions, 19 and be knowledgeable about palliative and hospice care.…”
Section: Introductionmentioning
confidence: 99%
“…Neste contexto, cartilhas educativas para cuidadores de pacientes oncológicos em cuidados paliativos visando desenvolver comportamentos positivos e aumentar a adesão ao reconhecimento dos sinais e sintomas, além da necessidade de um maior envolvimento do profissional, enfermeiro, com a educação em saúde e os pacientes oncológicos em cuidados paliativos. O Enfermeiro precisa compreender as práticas relacionadas à oncologia -cuidados paliativos -de maneira integral 16,17 . Deve-se estar disponível para um diálogo e sadio relacionamento com as questões de sobrecarga do cuidador, qualidade de vida do paciente oncológico, cuidados paliativos, morte e as dimensões éticas, sociais e culturais.…”
Section: Discussionunclassified